The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2001
DOI: 10.1614/0890-037x(2001)015[0068:rowrrr]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Wild Radish (Raphanus raphanistrum) to Acetolactate Synthase-Inhibiting Herbicides in the Western Australia Wheat Belt1

Abstract: Of 78 biotypes of wild radish (Raphanus raphanistrum) collected from Western Australia (WA), 42% were resistant and 14% intermediate to acetolactate synthase (ALS)-inhibiting herbicides. Based on the LD50 and GR50 ratios, the resistant biotype K96071 was 81-fold more resistant to chlorsulfuron and 114- to 116-fold more resistant to metosulam than the susceptible biotype K96041. More resistant biotypes were found in northern zones than in southern zones of WA. Resistant biotypes evolved after five applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 12 publications
3
45
0
2
Order By: Relevance
“…In an Australian weed survey in winter crops, R. raphanistrum was one of the three most widespread and abundant weeds, and the one whose spread was the most difficult to control, particularly in the southern and western regions where herbicide resistance has developed (See Section 11) (Alemseged et al 2001). Densities as low as 10 wild radish plants m -2 reduced wheat yields by up to 20% (Reeves et al 1981), with up to 50% reduction at densities of 80 wild radish plants m -2 (Hashem et al 2001a). The initial flush of germination followed by sporadic germination throughout a long growing season contributes to herbicide control problems in Australia (Donaldson 1986).…”
Section: Economic Importancementioning
confidence: 98%
See 2 more Smart Citations
“…In an Australian weed survey in winter crops, R. raphanistrum was one of the three most widespread and abundant weeds, and the one whose spread was the most difficult to control, particularly in the southern and western regions where herbicide resistance has developed (See Section 11) (Alemseged et al 2001). Densities as low as 10 wild radish plants m -2 reduced wheat yields by up to 20% (Reeves et al 1981), with up to 50% reduction at densities of 80 wild radish plants m -2 (Hashem et al 2001a). The initial flush of germination followed by sporadic germination throughout a long growing season contributes to herbicide control problems in Australia (Donaldson 1986).…”
Section: Economic Importancementioning
confidence: 98%
“…These primarily include biotypes resistant to acetolactate synthase (ALS)-inhibitors and/or resistant to photosystem II-inhibitors (triazines). ALSinhibitor R biotypes were first detected in 1997 after five applications of chlorsulfuron in a predominantly cereal to narrow-leafed lupin rotation (Hashem et al 2001a). By 1999, about 21% of wild radish populations in the western Australian wheat belt were chlorsulfuron-R (Walsh et al 2001), with about 13% of these cross-resistant to imidazolinones (another ALS-inhibitor) (Hashem and Dhammu 2002).…”
Section: Response To Herbicides and Other Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, other reports confirmed that application of pre-emergence and post-emergence herbicides ensured continuous effective control of weed species that emerged in several flushes and provided better yield over manual weeding even under minimum tillage practice [27,28]. But, the repeated use of herbicide with the same mode of action may leads to develop quick herbicide resistance in weeds which will make weed control more difficult [29][30][31][32]. Therefore, rotation of herbicides with different modes of action would benefit weed management in the longer term and minimise risks for development of herbicide resistance in weeds.…”
Section: Introductionmentioning
confidence: 99%
“…Now the susceptible biotype was controlled in 70 to 100%, with doses of 15 and 60 g i.a. ha -1 , respectively (Hashem et al, 2001). …”
Section: Resultsmentioning
confidence: 96%